OPTIMIZATION CONDITION EXTRACTION USED ENZYME WITH RESPONSE SURFACE METHODOLOGY TO EXTRACT ROSELLE PETALS (Hibiscus sabdariffa L.) - Mardiah, Mardiah; Hasanah, Rima Nidaul; Novidahlia, Noli; Hasan, A.E. Zainal (Universitas Djuanda, 2018)
Roselle petals can be made into extracts as a source of raw material for food products and other products. Previous research states that the use of pectinase and cellulase enzymes can increase the yield including the anthocyanin content. This study aims to optimize the extraction conditions of roselle flower petals (Hibiscus sabdariffa L.) using pectinase and cellulase enzymes by using Response Surface Methodology (RSM). The treatment conditions were using pectinase and cellulase enzyme (1: 1) with concentrations in the range between 500-1500 ppm, extraction temperature between 35-65 oC and extraction time between 30-90 minutes. Analysis of the best treatment was carried out on the yield level, anthocyanin content and total dissolved solids tested using central composite design, obtained R2 values for the three responses of 0.6. The results showed that based on the surface response, the optimum conditions of the best extraction of the rosella at the addition of enzyme concentration of 1000 ppm, extraction temperature of 50 oC and extraction time of 10 minutes. In this condition, the yield of dried extracts of rosella was 84,20%, anthocyanins content 479,70 mg/L and total soluble solid 2,13 oBrix.